2014
DOI: 10.1159/000365247
|View full text |Cite
|
Sign up to set email alerts
|

End-Word Dysfluencies in Young Children: A Clinical Report

Abstract: Objective: We report on 12 children with end-word dysfluencies (EWDs). Our aim was to document this little-reported type of dysfluency and to develop a possible explanation for them and how they relate to developmental stuttering. Method: Audio recordings were made for 9 of the 12 children in the study. The EWDs were identified by consensus of two specialist speech pathologists and confirmed on acoustic displays. A segment of participant 1's speech was transcribed, including phonetic transcription of EWDs. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…Five of the eight participants with word-final disfluencies scored above the SSI-4 threshold for at least very mild stuttering severity. These findings are in line with previous reports in autistic children (Scaler Scott et al, 2014) and give support to the hypothesis that stuttering-like and word-final disfluencies could share, at least to some extent, a similar etiology (MacMillan et al, 2014;Van Borsel et al 2005).…”
Section: Atypical Disfluenciessupporting
confidence: 93%
See 2 more Smart Citations
“…Five of the eight participants with word-final disfluencies scored above the SSI-4 threshold for at least very mild stuttering severity. These findings are in line with previous reports in autistic children (Scaler Scott et al, 2014) and give support to the hypothesis that stuttering-like and word-final disfluencies could share, at least to some extent, a similar etiology (MacMillan et al, 2014;Van Borsel et al 2005).…”
Section: Atypical Disfluenciessupporting
confidence: 93%
“…AD consist of repetitions and prolongations of the final parts of the word (word-final disfluencies), and mid/between-syllable insertions (e.g., Plexico et al, 2010;Sisskin, 2006). These patterns are not typically seen in developmental stuttering, where the disfluencies occur most often in the initial position of words, although some studies have also reported the occurrence of wordfinal disfluencies in children who stutter (Eichorn & Donnan, 2021;MacMillan et al, 2014;Scaler Scott et al, 2014).…”
Section: Atypical Disfluencies In Autistic Speakersmentioning
confidence: 99%
See 1 more Smart Citation
“…Al final de las palabras. Es muy raro, pero en ocasiones también ocurre el tartamudeo al final de las palabras [9].…”
Section: Momentos De La Tartamudezunclassified